The Impact of Environmental Pollution on Public Health: Global and Local Perspectives - Sri Ayu M. U. Buamona (Journal of Public Health Indonesian, 2025)
Environmental pollution represents one of the most significant public health threats at both global and local levels. This article analyzes the health impacts of air, water, and soil pollution using a Systematic Literature Review guided by PRISMA standards. Out of 578 identified studies, 84 articles met the eligibility criteria and were thematically synthesized. Findings show that air pollution contributes to increased cardiovascular diseases, respiratory disorders, and premature mortality. Water pollution elevates risks of infectious diseases and heavy metal exposure, while soil pollution affects food safety and long term exposure to toxic substances. In Indonesia, pollution is exacerbated by rapid urbanization, social inequality, and uneven environmental governance. The study emphasizes the need for cross sector strategies, enhanced monitoring capacity, and stronger health oriented environmental policies. These insights provide an evidence based foundation for designing interventions aimed at reducing pollution burdens and improving public health protection